Above-ground activity patterns of the semi-fossorial spiny rat Clyomys laticeps. Issue 4 (4th July 2018) - Ferrando, Claire P. Röpke; Leiner, Natália Oliveira
Abstract : Choosing a period to perform basic survival and breeding activities follows a trade-off between the costs and benefits associated to environmental and biotic demands, in which individuals try to maximize their fitness. Once the rodents have small tolerance to high temperatures, their activity patterns are usually thermally constrained. No information is registered about the activity patterns of semi-fossorial spiny rat Clyomys laticeps, which inhabits open physiognomies in savannah formations, hence dealing with large daily variations in temperature and humidity. In this way, the aim of this study was to describe the above-ground activity of free-living C. laticeps individuals, and test the hypothesis that their activity patterns are thermally restricted. By using camera traps set along one year, we demonstrated that individuals were more frequently active during night and dawn, which corresponded to the periods with lower temperatures. Hence, C. laticeps proved out to be nocturnal, with some degree of crepuscular activity. Its activity was restricted to temperatures between 10–25 °C, with an activity peak within 19–21 °C, thus supporting the hypothesis that their activity patterns are thermally constrained. The nocturnal activity of C. laticeps occurs in spite of predation risk in this period; thus, we suggest that timing of above-ground activity is probably a strategy to avoid thermal stress, and the benefits of being active in this period compensate the costs of predation.